Effect of hydrolysis temperature of Bacillus subtilis crude enzyme on sugar content and bioethanol production from date seeds - Trianik Widyaningrum; Merlina Suciati (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
This study aims to determine the effect of Bacillus subtilis crude enzyme temperature on reducing sugar content and bioethanol production from ajwa date seeds (Phoenix dactylifera L.). The study was conducted using an experimental method with a completely randomised design (CRD) of five temperature treatments, namely 34°C, 37°C, 40°C, 43°C, and 46°C, at pH 7 each with three replicates. Ajwa date seeds that had undergone pretreatment were hydrolysed using crude B. subtilis enzyme, then fermented with Zymomonas mobilis. The reducing sugar content was measured using the DNS method, while the bioethanol content was measured through distillation and an alcohol meter. The results showed that an increase in crude enzyme temperature had a significant effect on the reducing sugar and bioethanol content. A temperature of 46°C produced the highest reducing sugar content before fermentation at 3.89 g/mL, sugar content after fermentation at 2.47 g/mL, and the highest bioethanol content at 3.11%. Statistical analysis through regression and ANOVA showed a significant relationship between temperature and the two dependent variables, with R² values of 0.9248, 0.9514, and 0.9542, respectively. In conclusion, the temperature of B. subtilis crude enzyme is an important factor in optimising bioethanol production from ajwa date seeds. This study provides an alternative use of biomass waste for environmentally friendly renewable energy.